TOURISM MARKET IN THE WORLD AND IN RUSSIA: MODERN STATE AND DEVELOPMENT PROSPECTS - Tatyana N. Safronova; Olga A. Yabrova; Darina D. Shitova; Milena A. Khaneeva (Наука Красноярья, 2023)
Tourism plays a significant role in the GDP, job creation, and employment in many countries. According to the statistics of the World Travel & Tourism Council (WTTC) and Oxford Economics, there was a rapid recovery in the tourism sector in 2022, with its contribution to the global GDP increasing by 22% on an annual basis, reaching $7.7 trillion US dollars. There is a direct link between the trends in the development of the tourism industry and overall economic, technical, and social achievements. In recent years, the structure of tourist flows to the Russian Federation has changed significantly due to geopolitical and socio-economic factors.